Reconceptualizing Islamic Producer Behavior: Integrating Economic Rationality, Social Solidarity, and Spiritual Ethics in Micro-Enterprise Pricing - Syaichoni, Ahmad; Sujianto, Agus; Nurohman, Dede (Indonesian Journal Publisher, 2025)
This article aims to reconceptualize Islamic producer behavior by integrating economic rationality, social solidarity, and spiritual ethics within the context of micro enterprise pricing. The study seeks to address the persistent gap between Islamic normative principles and their practical implementation in everyday pricing decisions among Muslim micro and small enterprises. Using a qualitative descriptive approach based on a library study, data were collected through systematic review and analysis of recent and relevant academic literature focusing on Islamic economics, ethical pricing, and micro enterprise behavior. The analysis was conducted inductively through thematic identification, conceptual categorization, and theoretical synthesis to develop a comprehensive understanding of the phenomenon under study. The findings indicate that Islamic producer behavior is characterized by partial integration of the three dimensions. Economic rationality remains dominant, manifested in cost calculation, competition awareness, and profit considerations, yet is normatively oriented toward maslahah and falah rather than pure profit maximization. Social solidarity appears in the form of ethical pricing intentions and concern for community welfare, but its realization is often constrained by market structures and power imbalances. Spiritual ethics function as a moral foundation guiding intention and ethical awareness, although they are frequently practiced intuitively and lack systematic operationalization. These findings imply that Islamic producer behavior cannot be adequately explained through single dimensional models. The study concludes that a unified conceptual framework is required to bridge rational efficiency, social justice, and spiritual accountability. This reconceptualization contributes to the development of Islamic economic theory and provides practical insights for promoting ethical and sustainable pricing practices in micro enterprises.